Numerical modelling of propeller cavitation - Chua, Wilson (Nanyang Technological University, 2020)
Cavitation is a phenomenon that occurs on a marine propeller when it is in operation. The study of cavitation through means of numerical modelling allows propeller designers to understand this phenomenon and design the propeller accordingly to optimize the propeller’s performance. In this study, non-cavitating flows and cavitating flows will be modelled through series of marine propeller tests simulations using the software ANSYS Fluent. First, open water test simulations will be modelled for non-cavitating flows. A total of 10 simulations will be conducted the non-cavitating flows using the “SST k-ω turbulence models”. 5 simulations will be using 1st order discretization scheme and the other 5 simulations will be using 2nd order discretization scheme. Results of all 10 simulations were in agreement with the experiment data that were provided. Next, 3 different operating conditions, Case 1,2 and 3, of cavitation test were simulated. The “SST k-ω turbulence models” were used for all 3 cases and there were some discrepancies of the results when compared to experimental data. Case 2 were chosen to simulate an addition test, adopting the “k-kl-ω transition model”, which resulted in an improvement in the results.